Characterization Approaches Affect Asymmetric Load Predictions of Hexagonal Close-Packed Alloy - Garcia-Herrera, C (Elsevier Editora Ltda, 2023)
The anisotropic plasticity constants of the CPB06 criterion for Ti64, previously identified with experiments performed in all three dimensions, are applied here to evaluate the effect of the direct and inverse calibration strategies of the tensile-compression asymmetry parameter k on the predictive behavior of large deformations of the hexagonal close-packed (hcp) alloy. The direct calibration strategy is based on model fitting with experimental strain hardening data up to the onset of plastic instability. The inverse calibration strategy reduces prediction errors of the load-displacement curves of both the cylindrical bar tensile and the elliptical cylinder compression tests. The results provide interesting insights into the identification of the laws modeling large deformations of hcp materials. © 2023